Unraveling the Molecular Evolution of Blood Coagulation Genes in Fishes and Cetaceans - Mariz, João Pedro V.; Nery, Mariana F. (Frontiers in Marine Science, 2020)
Among the many physiological changes that occurred during the transition from an aquatic to a terrestrial lifestyle by early vertebrates, blood coagulation has an interesting history. Blood coagulation genes, originally composed of a single pathway in fishes, have expanded to include a second pathway in the evolution of terrestrial vertebrates. However, genes of this second pathway have been secondarily lost in many lineages, as is the case for cetaceans, which returned to the aquatic environment during their evolution. Herein, we investigated the selective pressures on blood coagulation genes in a phylogenetic framework, focusing on fishes and cetaceans. Taking advantage of the availability of the genetic sequences of many vertebrate lineages and using a combination of bioinformatic tools, our results showed a diverse history of gene losses and gains, with different selective pressures acting on different genes of the blood coagulation functional pathway. In addition, there was no evidence of a clear convergent molecular evolution between cetaceans and fishes, highlighting that there are many possible evolutionary mechanisms with regard to a functional pathway that involves many genes.